2013
DOI: 10.1155/2013/209529
|View full text |Cite
|
Sign up to set email alerts
|

Creep and Recovery Behavior of Compression Molded Low Density Polyethylene/Cellulose Composites

Abstract: Low density polyethylene (LDPE) is an important industrial material because it is durable, light-weight, easily processed and characteristically inert, but its everyday use is hazardous to the environment. The solution to this seems to consist of incorporation of biopolymers in the structure of LDPE to form composites. Compression molded composites at different cellulose loading were subjected to creep tests at 30, 40, 50, and 60 ∘ C. The samples were displaced for 12 minutes and allowed to recover for 12 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…From Figure 1, It can be deduced that strain rate continued to increase when the load is subjected to various temperatures over time, the higher the temperature, the closer it is to the glass transition temperature, the higher the strain, the faster the creep rate increases, this occurred due to the increase of the thermal kinetic energy and free volume in the creep of the matrix, the load stress level promotes a significant deformation and temperature demonstrates a high influence on strain results on the composites, the findings are in line with (Lechat et al, 2011;Lorandi et al, 2018;Riara et al, 2013;Zhang et al, 2017).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…From Figure 1, It can be deduced that strain rate continued to increase when the load is subjected to various temperatures over time, the higher the temperature, the closer it is to the glass transition temperature, the higher the strain, the faster the creep rate increases, this occurred due to the increase of the thermal kinetic energy and free volume in the creep of the matrix, the load stress level promotes a significant deformation and temperature demonstrates a high influence on strain results on the composites, the findings are in line with (Lechat et al, 2011;Lorandi et al, 2018;Riara et al, 2013;Zhang et al, 2017).…”
Section: Resultssupporting
confidence: 66%
“…Monticeli et al (2019) carried out creep/recovery and stress-relaxation tests in a standardized carbon fiber/epoxy composites, and the result confirmed that temperature is a determinant factor to creep and stress relaxation properties. Riara et al (2013) analyzed the creep and stress relaxation behavior of cellulose reinforced lowdensity polyethylene composites at different cellulose loading and temperature, the creep performance decreased with increase in temperature and improved with cellulose loading while creep modulus decreased with increase in time and temperature. Lechat et al (2011) studied the tensile and creep properties of polyethylene terephthalate and naphthalate fibers and there was a similarity in the creep rate value for both fibers.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was also reported by Banik et al who associated increasing temperature to higher polymer chain mobility leading to higher deformation. Also, increasing the temperature decreases the activation barrier for bond dissociation thus allowing molecular chains to untangle, slip, and reorient more easily . Table also shows that the retardation time τ increases with temperature and similar results were reported by Spoljaric et al for polypropylene‐microcrystalline cellulose composites.…”
Section: Resultssupporting
confidence: 83%
“…Low density polyethylene (LDPE) is used in several industries such as packaging, automotive, and housing equipment because of its advantages like durability, light weight, and easy processing. Unfortunately, this everyday use for large and varying applications makes this plastic hazardous to the environment due to the increasing volume of waste generated giving that petroleum‐based plastics are nonbiodegradable and produced using nonrenewable resources . Therefore, research of more appropriate applications is a goal currently pursued by plastics industries.…”
Section: Introductionmentioning
confidence: 99%
“…However, the two samples prepared by passing through the water bath at 25 and 65 °C behave almost similarly and show good resistance to deformation; The Fbr‐10–25°C sample shows a better recovery than Fbr‐10–65°C after removing the stress. The weak stress resistance of Fbr‐10–15°C sample compared to other samples can be attributed to the lack of development of the internal fibrillar structure and consequently the small contribution of fibrils in the elasticity of this composite 66 . As expected, with increasing relaxation time of the samples prepared by passing through a higher temperature water bath, these samples have a more stable morphology and their morphological changes are less during the creep test.…”
Section: Resultsmentioning
confidence: 54%